Integrated assessment of mechanical, microstructural, and thermal behaviour of a fly ash-stabilized earthen building material - Dogruyol, Murat; Gonul, Alisan; Tuncel, Oguz; Altun, Baris; Yilmaz, Abdullilah; Durmaz, Mahmut; Hansu, Fevzi (Elsevier, 2025)
This study investigates the influence of fly ash addition on the mechanical, microstructural, and thermal performance of Alker, a modern stabilized earth material composed of clay soil, gypsum, lime, and water. Alker is known for its enhanced strength and sustainability compared to traditional adobe, yet the integration of industrial by-products like fly ash remains underexplored. The research aims to identify an optimal mix design for strength and thermal efficiency by varying gypsum (5-15 %), lime (2.5-7.5 %), and fly ash (0-20 %) contents. The highest compressive strength of 4.15 MPa and the highest flexural strength of 1.54 MPa are achieved with a mixture containing 15 % gypsum, 5 % lime, and no fly ash. Microstructural analysis using scanning electron microscope-energy dispersive X-ray spectroscopy and X-ray diffraction confirmed that calcium-silicate- hydrate formation is responsible for strength development, whereas high fly ash content led to ettringite formation, causing microcracking and strength reduction. Thermal tests reveal that fly ash-containing samples exhibit lower thermal conductivity (0.505 W/mK), indicating improved insulation performance. The Genetic Aggregation Response Surface Methodology is employed for modelling, achieving a strong correlation with the experimental results (R2 = 0.995). The findings demonstrate that while fly ash reduces mechanical performance, it enhances thermal insulation. The fly ash-modified Alker emerges as a promising, adaptable material for sustainable low-rise building applications owing to this dual behaviour. The novelty of this work lies in the integrated evaluation of mechanical, microstructural, and thermal behaviour of fly ash -stabilized Alker, extending the literature by identifying optimal compositions and quantifying the trade-off between strength and thermal performance.
Keywords: Fly ash-stabilized Alker; Mechanical and thermal performance; Microstructural analysis; Sustainable building materials; Response surface methodology